Application of the rules of Al-Mubâsyir and Al-Mutasabbib in Islamic economic law (Mu'âmalah Mâliyyah) - Putra, Panji Adam Agus (International Journal Labs, 2024)
Legal maxims are essential in determining Islamic law and resolving branching legal problems. Scholars have formulated legal maxims to address issues related to mubâsyir and mutasabbib, as well as legal responsibility. This research aims to describe the legal maxims formulated by the ulama, particularly those related to mubâyir and mutasabbib, and analyze their application in sharia economic law. The research uses a normative juridical approach and uses secondary data for qualitative data analysis. The results show that the ulama have formulated at least five rules related to mubâyir and mutasabbib jurisprudence: (1) If the direct perpetrator and cause come together, the law relies on the direct perpetrator; (2) The direct perpetrator must be held responsible even if not intentional; (3) The cause is not responsible unless intentional; (4) An action is based on the perpetrator, not the person who orders it; and (5) An animal's error is not the owner's responsibility.